2021
DOI: 10.1002/acr.24430
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the New 2019 European League Against Rheumatism/American College of Rheumatology Classification Criteria for Systemic Lupus Erythematosus in Children and Young Adults

Abstract: Objective. To compare the diagnostic usefulness of the 2019 European League Against Rheumatism (EULAR)/ American College of Rheumatology (ACR) classification criteria for systemic lupus erythematosus (SLE) to that of the 1997 ACR classification criteria for SLE when applied to youths (age ≤21 years) with SLE. Methods. Data were extracted from electronic health records of patients followed at a large academic pediatric hospital. The treating rheumatologist's diagnosis of SLE served as the standard criterion for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…The absolute EULAR/ACR-2019 classification summary scores were higher in non-White than White cases. Sub-analysis showed that the sensitivity of the EULAR/ ACR-2019 criteria was not influenced by patient ethnicity, age or gender, whereas the sensitivity of the ACR-1997 criteria was significantly higher in non-White versus White cases [147]. Further studies are warranted to assess the performance of the EULAR/ACR-2019 criteria in children, in particular as younger children with jSLE have been shown to display less ANA positivity [20].…”
Section: Performance Of Classification Criteria For Sle In Jslementioning
confidence: 94%
“…The absolute EULAR/ACR-2019 classification summary scores were higher in non-White than White cases. Sub-analysis showed that the sensitivity of the EULAR/ ACR-2019 criteria was not influenced by patient ethnicity, age or gender, whereas the sensitivity of the ACR-1997 criteria was significantly higher in non-White versus White cases [147]. Further studies are warranted to assess the performance of the EULAR/ACR-2019 criteria in children, in particular as younger children with jSLE have been shown to display less ANA positivity [20].…”
Section: Performance Of Classification Criteria For Sle In Jslementioning
confidence: 94%
“…Three recent reports evaluated 2019-EULAR/ACR classification criteria in cSLE patients. The 2019-EULAR/ACR criteria effectively classify cSLE, irrespective of age, sex, and race, and these new criteria were more sensitive (85% vs 72%) with comparable specificity in youths with SLE compared with the 1997-ACR criteria (83% vs 87%) [ 91 ]. Another study showed the same sensitivity for 2019-EULAR/ACR and 2012-SLICC criteria (97.4%) and it was higher compared with the 1997-ACR criteria in cSLE patients (87.2%), with similar specificity between 2012-SLICC and 2019-EULAR/ACR criteria (98.4% and 99.7%, respectively) [ 92 ].…”
Section: Childhood-onset Systemic Lupus Erythematosus (Csle) Stratification and New Validated Classification Criteriamentioning
confidence: 99%
“…Two recent studies have assessed the performance of ACR/EULAR-2019 criteria in JSLE [ 10 , 11 ]. The first study included 122 JSLE patients and 89 controls (ANA positive with other rheumatic diseases).…”
Section: Discussionmentioning
confidence: 99%
“…Data on performance of ACR/EULAR-2019 criteria in JSLE is limited to two relatively small cohorts that both suggested limited specificity when compared with ACR-1997 or SLICC-2012 criteria [ 10 , 11 ]. These studies did not include longitudinal assessment of the ACR/EULAR-2019 criteria.…”
Section: Introductionmentioning
confidence: 99%